Direct imaging of transient interference in a single-mode waveguide using near-field scanning optical microscopy - Lear, Kevin L., author; Dandy, David S., author; Stephens, Matthew D., author; Yuan, Guang Wei, author; IEEE, publisher (Colorado State University. Libraries, 2005)
Near-field scanning optical microscopy was used to image transient interference between the guided mode and a leaky mode induced in a single-mode waveguide due to a localized adlayer. The observed field response in the adlayer region as well as the period and decay length of the subsequent interference are in good agreement with beam propagation calculations. The transient interference impacts the element spacing in local evanescent array coupled sensors.
Keywords: waveguide; evanescent field; leaky mode; near-field scanning optical microscopy (NSOM); biosensor; optical interference